Odpowiedzi

Najlepsza Odpowiedź!
2010-03-10T21:01:25+01:00
A) 2a² + 7 = a (1 + 2a)
2a²+7=a+2a²
2a²-2a²-a=-7
-a=-7
a=7

b) 3a (a - 1) = a (3a -2)
3a²-3a=3a²-2a
3a²-3a²+2a-3a=0
-a=0
a=0

c) 2a - a² + a (2 + a) = a + 18
2a-a²+2a+a²=a+18
2a+2a-a=18
3a=18 /:3
a=6

d) a² + 5 = 5a (0,2a + 3)
a²+5=a²+15a
a²-a²-15a=-5
-15a=-5 /:-15
a=⅓
11 4 11
2010-03-10T21:03:32+01:00
A) 2a² + 7 = a (1 + 2a)
2a² + 7 = a + 2a²
a = 7
b) 3a (a - 1) = a (3a -2)
3a²-3a=3a²-2a
a=0
c) 2a - a² + a (2 + a) = a + 18
2a-a²+2a+a²-a=18
3a=18
a=6
d) a² + 5 = 5a (0,2a + 3)
a²+5-a²=15a
5=15a
a=1/3
4 4 4